Magnetic Resonance Imaging/Ultrasound–Fusion Biopsy Significantly Upgrades Prostate Cancer Versus Systematic 12-core Transrectal Ultrasound Biopsy - Siddiqui, M. Minhaj; Rais-Bahrami, Soroush; Truong, Hong; Stamatakis, Lambros; Vourganti, Srinivas; Nix, Jeffrey; Hoang, Anthony N.; Walton-Diaz, Annerleim; Shuch, Brian; Weintraub, Michael; Kruecker, Jochen; Amalou, Hayet; et al. (European urology, 2013)
Gleason scores from standard, 12-core prostate biopsies are upgraded historically in 25−33% of patients. Multiparametric prostate magnetic resonance imaging (MP-MRI) with ultrasound (US)-targeted fusion biopsy may better sample the true gland pathology. The rate of Gleason score upgrading from an MRI/US-fusion-guided prostate-biopsy platform is compared with a standard 12-core biopsy regimen alone. There were 582 subjects enrolled from August 2007 through August 2012 in a prospective trial comparing systematic, extended 12-core transrectal ultrasound biopsies to targeted MRI/US-fusion-guided prostate biopsies performed during the same biopsy session. The highest Gleason score from each biopsy method was compared. An MRI/US-fusion-guided platform with electromagnetic tracking was used for the performance of the fusion-guided biopsies. A diagnosis of prostate cancer (PCa) was made in 315 (54%) of the patients. Addition of targeted biopsy led to Gleason upgrading in 81 (32%) cases. Targeted biopsy detected 67% more Gleason ≥4+3 tumors than 12-core biopsy alone and missed 36% of Gleason ≤3+4 tumors, thus mitigating the detection of lower-grade disease. Conversely, 12-core biopsy led to upgrading in 67 (26%) cases over targeted biopsy alone but only detected 8% more Gleason ≥4+3 tumors. On multivariate analysis, MP-MRI suspicion was associated with Gleason score upgrading in the targeted lesions (p<0.001). The main limitation of this study was that definitive pathology from radical prostatectomy was not available. MRI/US-fusion-guided biopsy upgrades and detects PCa of higher Gleason score in 32% of patients compared with traditional 12-core biopsy alone. Targeted biopsy technique preferentially detects higher-grade PCa while missing lower-grade tumors. Magnetic resonance imaging/ultrasound-fusion guided biopsies upgraded Gleason score in 32% of prostate cancer cases and led to a 67% rate of increased diagnosis of high-grade tumors versus 12-core biopsy alone. Targeted biopsy missed diagnosis of lower-grade tumors in 36% of cases.